Uma caracterização da aplicação de princípios de Maria Montessori a partir do livro Psico-Aritmética (1934) - Santos, Helen Kaline Amorim (2023)
Maria Montessori (1870-1952), an Italian physician and educator, was one of the forerunners of methodologies for teaching “abnormal” children. He idealized a teaching method that became known as the Montessori method, for those who had some type of disability. Later, the method developed by the educator started to be used for all children, since it was identified that they all had the same ability to learn. For this, Montessori took as a basis studies by Jean Itard (1774-1838) and Edouard Séguin (1812-1880) and perfected to build the methodological proposal he defended, he elaborated materials in wood and established in his thesis that all children should have the right principles, namely: individuality, freedom and independence. The option adopted for the development of the research was to use one of the books produced by Montessori: Psico-aritmética (1934). This was chosen as a source because it contains a greater number of figures representing the materials prepared by the educator. Before carrying out the research, a mapping of theses and dissertations already developed on Montessori formation and performance trajectories, on Montessorian materials and methodology, was carried out, the works considered were: Rezende (2021), Campos (2017), Rosa (2017), Santos (2015), Fernandes (2020), Torrez (2018) and Molon (2015). After examining these researches, the following question was taken as a guide: how are the principles defined by Montessori present in the guidelines in the book Psico-aritmética (1934) produced for the teaching of arithmetic? To answer this question, the objective was to characterize the guidelines for the application of Maria Montessori's principles for teaching arithmetic based on the book Psicoaritmética (1934). By examining the book, it was possible to identify some teaching materials, such as: prismatic rods, spindles, demonstrative material of the decimal system, beads and a table of rods. Just as it was identified that the principles of independence, freedom and individuality are present in the guidelines proposed in the book Psico-aritmética (1934) based on the use of materials. For example, guidance on using the decimal system includes the representation of quantity; grouping and decomposition of numbers; and the four arithmetic operations. The educator guided the use of the material with its photographic representation and the usefulness of the method based on the principles, the way the adult should act, and what she expected the child to learn in relation to arithmetic knowledge.